Tight Spaces, Tighter Signals: Spatial Constraints as Drivers of Peripheral Myelination - Luca Bartesaghi; Basilio Giangreco; Vanessa Chiappini; Maria Fernanda Veloz Castillo; Martina Monaco; Jean-Jaques Médard; Giovanna Gambarotta; Marco Agus; Corrado Calì (Cells, 2025)
Peripheral myelination is driven by the intricate interplay between Schwann cells and axons, coordinated through molecular signaling and the structural organization of their shared environment. While the biochemical regulation of this process has been extensively studied, the influence of spatial architecture and mechanical cues remains poorly understood. Here, we use in vitro co-culture models—featuring microfluidic devices and hydrogel-based scaffolds—to explore how extracellular organization, cellular density, and spatial constraints shape Schwann cell behavior. Our results show that (i) pro-myelinating effects triggered by ascorbic acid administration is distally propagated along axons in Schwann cell-DRG co-cultures, (ii) ascorbic acid modulates Neuregulin-1 expression, (iii) a critical threshold of cellular density is required to support proper Schwann cell differentiation and myelin formation, and (iv) spatial confinement promotes myelination in the absence of ascorbic acid. Together, these findings highlight how spatial and structural parameters regulate the cellular and molecular events underlying peripheral myelination, offering new physiologically relevant models of myelination and opening new avenues for peripheral nerve repair strategies.